2014
DOI: 10.1039/c4ra09769f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive determination of bisphenol A in water by inhibition of copper nanoclusters-enhanced chemiluminescence from the luminol–KMnO4system

Abstract: In the present work, a highly sensitive chemiluminescence (CL) system for determination of trace bisphenol A (BPA) was established. The method was based on the inhibitory effect of luminol CL by BPA on the Cu NCs-enhanced luminol-KMnO 4 CL system for the first time. Water-soluble Cu NCs capped with BSA were synthesized. Under the optimized conditions, the inhibited CL intensity was proportional to the concentration of BPA ranging from 1.0 Â 10 À9 to 1.0 Â 10 À5 mol L À1 , with a detection limit (3s) of 1.2 Â 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Recently, Chen's group [81,82,91] reported that both Au NCs and Cu NCs could greatly enhance the CL intensities of luminol-H 2 O 2 and luminol-KMnO 4 systems. They attributed this to the catalysis of Au NCs and Cu NCs on the radical generation (such as O 2 •-, OH • ) and electron-transfer processes during the luminol CL reaction (Figure 1).…”
Section: Metal-nanocluster-amplified Luminol CL Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Chen's group [81,82,91] reported that both Au NCs and Cu NCs could greatly enhance the CL intensities of luminol-H 2 O 2 and luminol-KMnO 4 systems. They attributed this to the catalysis of Au NCs and Cu NCs on the radical generation (such as O 2 •-, OH • ) and electron-transfer processes during the luminol CL reaction (Figure 1).…”
Section: Metal-nanocluster-amplified Luminol CL Systemmentioning
confidence: 99%
“…In 2005, Au nanoparticles-amplified luminol CL was reported by Cui et al [86]. Since then, a series of different CL systems based on Au, Ag, Pt, ZnO nanoparticles has been investigated [87][88][89][90] and it was found that some metal NCs (e.g., Au, Ag, Cu, Zn/Cu alloy NCs ) could enhance intensity of CL systems including luminol-H 2 O 2 [81,91], luminol-KMnO 4 [82], NaNO 2 -H 2 O 2 [78], Ce(IV)-Na 2 SO 3 [70,71], NaHCO 3 -H 2 O 2 [83].…”
Section: Chemiluminescence Applications Of Metal Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of detection (LOD), defined as the minimum dose distinguishable from 0 or the minimum detected concentration (mean − 3SD of zero standard, eight replicates), of BPA was 2.9 ng/mL. Compared with the reported CL analytical methods or FL homogenous immunoassay (Table 1), the proposed method showed the relatively higher sensitivity than the others except the report of [27,43]. Moreover, it also showed the highest rapidity and can achieve the high-throughput screening detection.…”
Section: Assay Sensitivity and Linear Rangementioning
confidence: 99%
“…Under optimum conditions, the CL intensity displayed a calibration response for H 2 O 2 over 3 orders of magnitude from 0.1 to 150 mM with a LOD of 0.03 mM. In another work[63], based on inhibition effect of bisphenol A (BPA) on Cu NCs enhanced luminol-KMnO 4 CL system, a highly sensitive CL method was developed for the determination of BPA in aqueous samples. The detection for BPA is 0.12 nM.5.…”
mentioning
confidence: 98%